Headmasters' transformational leadership and their relationship with teachers' job satisfaction and teachers' commitments - Abdul Wahab, Jamalullail; Mohd Fuad, Che Fuzlina; Ismail, Hazita; Majid, Samsidah (Canadian Center of Science and Education, 2014)
This study aimed to determine the level of transformational leadership practices by headmasters in the primary national schools in the district of Temerloh, Malaysia. The four dimensions of Transformational Leadership studied were fostering the ideal influence, inspirational motivation, intellectual stimulating and individual consideration. The study also looks at the level of teachers’ job satisfaction and teachers ‘commitments as well as the relationship with the practice of transformational leadership by headmasters. The respondents consisted of 240 teachers working in 10 primary schools in the district of Temerloh, Pahang. The data obtained was processed using SSPS program version 12.0 and were analyzed using descriptive and multivariate. The result of the study showed that the practice of transformational leadership by headmasters in the district of Temerloh, Malaysia, was at a high level and teacher’s job satisfaction was high too, and there exist a significant relation between the level of transformation leadership and teachers’ job satisfaction while teachers’ commitments were average. However, the results of the study showed a significant relation between the level of transformational leadership and teachers work commitment. The implication of this study is that leaders should always ensure their high performance leadership to have a significant relationship with staff’s satisfaction and school staff’s commitment.